The Function of Class Management in The Improving Effectiveness of Learning Aqidah in MTs Al-Hidayah Betoyokauman Gresik - Asrori Asrori (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
The success of teaching in the sense of achieving teaching objectives, it really depends on the ability of the class. Classes that can create situations to enable students to learn well are a starting point for teaching success. And students can learn well in a normal atmosphere without pressure and in conditions that are stimulating to learn. They need guidance and assistance to understand teaching materials in various learning activities. In learning activities, students need something that allows them to communicate well with the teacher, with friends and with the surrounding environment. This type of research used in this research is a case study. In this case, explaining that a case study is a research conducted on a unified system. This unit can be like a program, activity, event, or group of individuals who are bound by a certain place, time or bond. In short, a case study is a research that is directed to collect data, take meaning, gain understanding of the case. From the results of the author's research at MTs Al-Hidayah Betoyo Kauman Gresik regarding "the function of classroom management in improving the effectiveness of Islamic religious education learning" are: the steps of implementing classroom management in MTs Al-Hidayah Betoyo Kauman Gresik are as follows: Increasing self-awareness as a teacher and educator. Selection of appropriate learning methods and media. Giving a reprimand / question for students who violate the classroom rules. Pay attention to all student behavior while in class when receiving lessons. Group students who have problems learning difficulties in Islamic religious education and students who have problems. Mengenai classroom management functions to improve the effectiveness of learning in MTs Al-Hidayah Betoyo Kauman Gresik is very important to be noticed by a teacher, especially teachers of Islamic religious education. There are four functions of the teacher as the class manager as follows: Planning this is to arrange a program to be achieved by the teacher in improving the effectiveness of learning in MTs Al-Hidayah Betoyo Kauman Gresik. Organizing this is grouping students in the teaching and learning process in the classroom in order to achieve predetermined educational goals. Like the Aqidah  teacher at MTs Al-Hidayah Betoyo Kauman Gresik when teaching using methods, for example the demonstration method. To lead this is the teacher can guide, encourage the behavior of students in MTs Al-Hidayah Betoyo Kauman Gresik so that they will be ready to realize their learning goals. Supervise, by supervising the teacher as the manager can pay attention to the behavior of students in MTs Al-Hidayah Betoyo Kauman Gresik so as to achieve the stated learning goals.   Keywords: Classroom Management Functions, Effectiveness of Aqidah Learning